The Transformation of Money in Islamic Civilization: The Journey of the Monetary System From Precious Metals to Digital Money - Mega Kilawati (al-Afkar, Journal For Islamic Studies, 2025)
This research explores the evolution of money in Islamic civilization, from the dinar and dirham based on precious metals to the innovation of paper currency in the colonial era, and finally to the modern era with the advent of electronic money. Money, in the perspective of Islamic economics, is not only a medium of exchange, but also an instrument for maintaining economic justice and social balance. This study uses the literature method to trace the changes in the Islamic monetary system from the perspective of history and sharia law. The results of the study show that electronic money provides convenience and efficiency, but its legality aspects need to be carefully reviewed in the context of sharia. In addition, digital money brings new challenges related to volatility and speculation, which has led to debate among scholars regarding its validity in transactions in accordance with Islamic law. In an effort to seek clarity, a deeper study is needed to assess the potential and risks of digital money in the Islamic economic system.